Legal Certainty Regarding the Rights of Secured Creditors to Execute Collateral in Bankruptcy Proceedings in Indonesia - Sari, Ayu Puspita; Gunadi, Ariawan (Dinasti Research, 2025)
Separate Creditors as Holders of Security Rights possess a preferential claim over the secured collateral. However, under bankruptcy law, their rights to execute and auction the collateral are subject to statutory limitations. In practice, Supreme Court Decision No. 521 K/Pdt.Sus-Pailit/2021 and Supreme Court Decision No. 527 K/Pdt.Sus-Pailit/2020 have provided divergent interpretations regarding the execution rights of Separate Creditors over their collateral once the debtor has been declared bankrupt. The core issues examined in this research are: (1) How legal certainty is afforded to the execution rights of Separate Creditors pursuant to Supreme Court Decisions No. 521 K/Pdt.Sus-Pailit/2021 and No. 527 K/Pdt.Sus-Pailit/2020; and (2) What legal consequences arise for Separate Creditors who fail to execute their collateral under Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU). This study employs normative legal research using a statutory approach and case-based analysis, focusing on judicial interpretations of bankruptcy decisions affecting the execution rights of Separate Creditors. The research relies on secondary data obtained through literature review and applies qualitative analytical methods. Separate Creditors are granted a two-month period following insolvency to initiate execution proceedings by filing a public auction request with the KPKNL, which is calculated from the commencement of the execution process not from the completion of the auction. Furthermore, the rights of Separate Creditors are not absolute, as they are constrained by a statutory stay period of 90 (ninety) days from the date the debtor is declared bankrupt. During this stay period, the Curator is entitled to demand that the collateral held by Separate Creditors be transferred to the Curator for sale either through public auction or private sale, under the supervision of the Supervisory Judge. It is therefore necessary to revise Law No. 37 of 2004 to clarify the scope of authority held by Separate Creditors in executing collateral, and to establish a digital oversight mechanism for curatorial functions to ensure transparency and accountability when collateral is handed over to the Curator for auction.